Animation Films and Their Impact on the Behavior of Kindergarten Child from the Point of View of Mothers (Journal Of Educational and Psychological Researches, 2022)
The child spends several hours watching animated films, which affect their behavior negatively and positively. This calls parents to monitor what their children are watching, to show them the serious risks of some violent films, and to direct them toward choosing both positive and educational programs that develop their positive behavior. This study aimed to explore the positive and negative effects of watching animation films as well as to identify the role animation films in increasing the cognitive knowledge of kindergarteners. To do this, the descriptive and analytical methods were used. A questionnaire was adopted as a tool for data collection. A scale of (45) items classified into three categories was applied on  the random research sample of 200 mothers of children enrolled in kindergartens in Baghdad, within  Karkh district (Directorate of Education in Karkh 1 and the Directorate of Education in Karkh 2). The findings of this study revealed that animation films have many positive and negative effects that significantly can be observed on the behavior of kindergarteners. Moreover, Animation films play an important role in increasing the knowledge of kindergarten children. The study came out with a conclusion; a large percentage of children in our society are addicted to watching animated films. The most important recommendations and proposals recommended by the study are: 1. Parents should work on organizing their children's hours, such as reducing their hours of watching animation films, which takes more time than other needs such as playing, sleeping, eating, and reviewing their lessons. 2. Parents must educate themselves by recognizing the effects of animation flims on children to avoid their risks. 3. The correct and serious awareness of individuals in society about the extent of the negative effects of television and the risks of the content of programs that threaten the ethics, beliefs, culture,  and health of our children.